HEXOKINASES IN BREAST CANCER - Kharitonov, S.; Zikiriahodzhaev, A.; Ermoshchenkova, M.; Sukhot’ko, A.; Fedorova, M.; Pudova, E.; Alekseev, B.; Kaprin, A.; Kudryavtseva, A. (International Journal of Biosciences and Biotechnology; Vol 4 No 2 (2017), 2017)
Hexokinases are one of the key enzymes involved in the process of glycolysis. The level of expression of hexokinases is widely studied in breast cancer as a possible marker of unfavorable prognosis and aggressiveness of tumors. The level of expression of hexokinase may reflect the level of glycolysis activation and, thus, indicate samples with the most altered cellular metabolism.